KAJIAN TERHADAP POLA HUBUNGAN ANTARA PROFITABILITAS DENGAN TINGKAT PENGGUNAAN HUTANG PADA INDUSTRI MANUFAKTUR - Mulya, Yudhia (Universitas Pakuan, 2011)
ABSTRACTChoosing the appropriate level of debt and equity is an on-going process as long as there are continuous changing of market conditions, tax rules and competitions. This study examines the pattern of relationship between profitability and usage of debt for companies listed at Jakarta Stock Exchange. This is a cross-sectional study, which used 122 firms selected from manufacturing industry in period of December 2005. Return on assets is used to measure profitability and with correlation analysis, this study tried to find the relationship between profitability and debt ratio as a measure of usage of debt. Pearson coefficient correlation indicate that there is an inverse relationship between profitability and usage of debt wherein the lower the profitability, the higher the usage of debt, or vice versa, but the relationship is weak. Keywords: insolvent, profitability, debt ratio, pecking order theory